Elevated immune response in the brain of autistic patients - Li, Xiaohong; Chauhan, Abha; Sheikh, Ashfaq M.; Patil, Sangita; Chauhan, Ved; Li, Xiu-Min; Ji, Lina; Brown, Ted; Malik, Mazhar (Journal of neuroimmunology, 2009)
This study determined immune activities in the brain of ASD patients and matched normal subjects by examining cytokines in the brain tissue. Our results showed that proinflammatory cytokines (TNF-α, IL-6 and GM-CSF), Th1 cytokine (IFN-γ) and chemokine (IL-8) were significantly increased in the brains of ASD patients compared with the controls. However the Th2 cytokines (IL-4, IL-5 and IL-10) showed no significant difference. The Th1/Th2 ratio was also significantly increased in ASD patients. Conclusion: ASD patients displayed an increased innate and adaptive immune response through the Th1 pathway, suggesting that localized brain inflammation and autoimmune disorder may be involved in the pathogenesis of ASD.